2017
DOI: 10.1007/s00261-017-1144-1
|View full text |Cite
|
Sign up to set email alerts
|

Texture analysis as a radiomic marker for differentiating renal tumors

Abstract: Texture analysis is a promising non-invasive tool for distinguishing renal tumors on CT images. These results were further improved upon application of machine learning, and support the further development of texture analysis as a quantitative biomarker for distinguishing various renal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(90 citation statements)
references
References 27 publications
2
84
0
4
Order By: Relevance
“…Because chRCC and RO are relatively rare compared to renal clear cell and renal papillary cell carcinoma, radiomic studies of renal tumors are focused on relatively common renal tumors. Studies on the most frequently occurring renal clear cell carcinoma have focused on different aspects such as preoperative diagnosis [19][20][21][22], tumor grade [23], prognostic evaluation [24], and molecular analysis of the cancer genes [25][26][27]. Yu et al [20] extracted the texture features of four types of renal tumors, including renal clear cell carcinoma, renal papillary cell carcinoma, chRCC, and RO.…”
Section: Discussionmentioning
confidence: 99%
“…Because chRCC and RO are relatively rare compared to renal clear cell and renal papillary cell carcinoma, radiomic studies of renal tumors are focused on relatively common renal tumors. Studies on the most frequently occurring renal clear cell carcinoma have focused on different aspects such as preoperative diagnosis [19][20][21][22], tumor grade [23], prognostic evaluation [24], and molecular analysis of the cancer genes [25][26][27]. Yu et al [20] extracted the texture features of four types of renal tumors, including renal clear cell carcinoma, renal papillary cell carcinoma, chRCC, and RO.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics, a method that processes imaging data according to various mathematical algorithms, allows for extraction of data that cannot be detected by the human observer. These algorithms are promising for the characterization of tumor type and behavior of some cancers [ 9 , 10 ]. Neuro-oncologists have successfully applied radiomics in the survival assessment of glioblastoma [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The emerging concept that biomedical images contain ‘hidden’ information about the underlying tissue biology that can be revealed via quantitative image analysis, an approach known as radiomics, has prompted the application of automated image analysis tools in renal tumours [68]. Early retrospective data have suggested that texture analysis of CT images combined with machine learning could distinguish RCC subtypes with an AUC > 0.90, warranting prospective investigation [69]. Molecular imaging with 99m technetium–sestamibi single photon emission computed tomography/computed tomography ( 99m Tc-MIBI SPECT/CT) has also been used to differentiate oncocytomas and indolent hybrid oncocytic/chromophobe tumours from other more aggressive malignant small renal tumours.…”
Section: Resultsmentioning
confidence: 99%